Knowledge and Attitude of 3rd Year Medical Students regarding Post Mortem Examination - Ahmad, Mushtaq; Rahman, Md Fashiur; Rahman, Farial Naima; Rahman, Md Afzalur (Journal of Armed Forces Medical College, Bangladesh, 2016)
Introduction: Post mortem examination is a process which is required to establish the exact cause of death in sudden, suspicious or unnatural cases. It determines the mode, manner and time passed since death. Objective: To explore the knowledge and attitude of 3rd year medical students regarding post mortem examination at the very beginning of their para clinical course study. Materials and Methods: This descriptive cross sectional study was performed at Armed Forces Medical College, Dhaka during the period of July to September 2016. One hundred fifteen 3rd year students were selected by purposive and convenient method and asked to respond anonymously to a 18 item selfadministered, predesigned, pretested multiple choice questionnaire which dealt with their views on autopsy practice, the knowledge procedure, attitude and perception towards post mortem examination. Ethical permission of authority concerned and verbal consent was obtained from every respondent students. Results: In this study, 108(93.91 %) students gave positive answer about the requirement of autopsy in unnatural death cases. A large number of students 57(49.56%) did not know about the types of autopsy, but more than half 67(58.26%) knew about virtual autopsy. Seventy two (62.61%) answered that heart is the organ sent for histopathological examination and majority 71(61.74%) could identify the viscera sent for chemical analysis. But most of them 65(56.52%) had wrong idea about the laboratory for chemical analysis. Also 70(60.87%) thought that formalin is used for preservation of viscera. Majority students 88(76.52%) answered that autopsy is performed to detect the cause of death. Greater part of respondent 98(85.22%) also said postmortem examination is neither harassment to victim’s relatives and nor disrespect to a dead body. Most of the students 113(98.26%) answered that observation of post mortem examination should be part of MBBS course curriculum and all 115(100%) gave positive response about utility of this chapter in their course studies. Forty one (35.65%) came to know about autopsy from medical books, followed by 35(30.44%) from newspaper/ story books. Almost all 113(98.26%) did not watch any autopsy before their admission to medical college. A greater part of students 74(64.35%) did not know whether autopsy cause any disfigurement of dead bodies. In present study 102(88.69%) students showed positive attitude to have post mortem examination of relatives if required. Majority of samples thought post mortem is not required in putrefied body and 93(80.87%) answered that body can be preserved at mortuary cooler after post mortem when required. Conclusion: Post mortem is an integral part of Forensic Medicine course curriculum. Teaching professionals should give more emphasis to make this chapter more interesting to the medical students. Journal of Armed Forces Medical College Bangladesh Vol.12(2) 2016: 9-14